Integrasi Pembelajaran Al Qur’an Hadits dan Sains Melalui Model Discovery Learning - Izzatul Aini; Anita Puji Astutik (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this research is to answer the problems that are in SMA Al Islamiyah Putat Tanggulangin, Sidoarjo. According to the results of observations made by researchers, one of the problems in the school is environmental cleanliness, where there is no cleanliness movement yet so the authors create a learning plan by combining Al-Quran hadith learning in class XII and Science in class X using the discovery model. learning. In this study using descriptive qualitative research, the main data source is the teaching material of Al-Quran hadith class XII and Science in class X with the theme of preserving the environment and biodiversity. The results of this study are that the use of the discovery learning model has a very positive impact on solving the school's problems. The results obtained when using this model are that students have more awareness in disposing of waste, know how to sort waste between organic and non-organic waste, have religious and scientific knowledge related to environmental preservation, and think critically about surrounding problems.